Cattle Encephalon Glycoside and Ignotin Reduce Early Brain Injury and Cognitive Dysfunction after Subarachnoid Hemorrhage in Rats. (15th September 2018) - Ma, Kang; Li, Rongwei; Zhao, Hengli; Qu, Jie; Mu, Ning; Liu, Xin; Wang, Shi; Yang, Chuanyan; Feng, Hua; Tan, Liang; Li, Fei
Highlights: Multitarget-drug cattle encephalon glycoside and ignotin (CEGI) has a neuroprotective effect in SAH. CEGI significantly reduced hippocampus neuronal apoptosis in early brain injury (EBI). CEGI remarkably reduced the level of cleaved caspase-3, Bax, cytochrome c, and PUMA, and amplified the expression of Bcl-2. CEGI facilitated cognitive dysfunction recovery. Abstract: Subarachnoid hemorrhage (SAH) is a well-known hemorrhagic stroke with high rates of morbidity and mortality where patients frequently experience cognitive dysfunction. This study explores a potential treatment for cognitive dysfunction following SAH with the demonstration that multi-target drug cattle encephalon glycoside and ignotin (CEGI) can relieve cognitive dysfunction by decreasing hippocampal neuron apoptosis following SAH in rats. Experimentally, 110 male SD rats were separated at random into Sham (20), SAH + Vehicle (30), SAH + 4 ml/kg CEGI (30), and SAH + 1 ml/kg CEGI groups (30) and an endovascular perforation model was created to induce SAH. We discovered that the number of TUNEL-positive neurons in the hippocampus was markedly decreased in SAH + 4 ml/kg and SAH + 1 ml/kg CEGI groups compared to the SAH + Vehicle group. This finding was associated with an observed decrease in Bax/Bcl-2 ratio, cytochrome-c and PUMA expression, and the suppression of caspase-3 activation following SAH. In Morris water maze tests, the SAH + 4 ml/kg CEGI group demonstrated a decreased escape latency time and increase in time spent in the target quadrant as well as crossing times of platform region. These results indicate that high doses of CEGI can decrease hippocampal neuron apoptosis and relieve cognitive dysfunction in rats, suggesting that multitarget-drug CEGI exhibits a neuroprotective effect in SAH via the mitochondrial apoptosis pathway.